Complex evolutionary dynamics in simple genomes: the paradoxical survival of intracellular symbiotic bacteria - Toft, Christina (Trinity College (Dublin, Ireland). Department of Genetics, 2009)
Symbiosis is one of the ways in which nature has been able to generate biological innovation by fusing two organisms with different complexities. Because of these differing complexities, many problems for both organisms had to be overcome to succeed in their biological marriage, including their metabolic communication and the coupling of their population dynamics. An example of a successful co-living is best represented by the relationship between strict endo-cellular symbiotic bacteria and insects, such as the case of symbionts of aphids and those of carpenter ants. Due to their intergenerational transmission dynamics, these bacteria present high mutational load, downsized genomes and unstable proteomes. Despite this the symbiotic relationships between these organisms have survived for tens of millions of years. However, the mechanism underlying this survival remains an evolutionary puzzle. In this thesis a comprehensive whole genome comparative analysis was carried out between intracellular symbionts of insects and their close free-living relatives. To achieve an exhaustive comparative genomics analysis pre-existing and novel tools were used to investigate the evolutionary dynamics of endosymbionts and quantify the shift in the selection-drift balance. To contribute to the understanding of the evolutionary mechanisms enabling the survival of endosymbiosis, extensive evolutionary analyses were conducted on different phenomena as yet poorly examined. The main questions that this thesis aimed at answering were: How did mutations accumulate in endosymbiotic bacterial genomes? What are the evolutionary rules these mutations follow? What is the selective mechanism(s) whereby selection counteracted the destabilising effects of slightly deleterious mutations? Deciphering the main genome dynamics, the evolution of redundancy, divergence and reshaping of the mutational and functional landscapes, the role of structural constraints and the interaction between mutations’ effects have been among the key points addressed in this thesis. Contradictary to the believe of the scientific community, the main finding of this theses is that mutations are not fixed randomly in endosymbiotic bacterial proteins despite their stochastic emergence but rather follow a clear evolutionary pattern devoted to the physico-chemical and thermodynamic rules of nature. Endosymbiotic bacteria are not exempt from following selection rules observed in free-living organisms, this is for example observed with the strong signal of translational robustness of genes which carry out important and fundamental cellular processes for the bacterium or its host. The adaptation of the endosymbiotic bacteria to their new environment has created new requirements such as export of metabolites from the bacterium to the host. This could be possible by re-use of existing biological material instead of inventing new material previously dedicated to cell motility. This thesis shows that flagella genes have reduced their complex proteomic apparatus to the necessary genes for protein export in a reverse evolution way. This reuse and/or specialisation of proteins do not only occur with some of the flagellar genes. One of the other results in this thesis indicates that endosymbiotic bacteria have undergone genome wide functional divergence events, fundamentally affecting genes whose protein products in endosymbiotic bacteria are dependent not only on the ecological requirements of the bacterium but also upon those of their host. The population genetics conditions under which the endosymbiotic bacteria populations of insect live have facilitated the neutral fixation by genetic drift of slightly deleterious mutations. These mutations are mostly destabilising and would be doomed under strong selective pressures. Endosymbiotic bacteria need to use other means to minimise the relative biological fitness decline of these mutations. One of the main findings of this thesis is that endosymbiotic bacteria of insects have evolved towards utilising two main ingenious mechanisms to ameliorate the effects of slightly deleterious mutations: i) one direct mechanism provided by the ubiquitous and over-expressed heat-shock protein GroEL, to ensure correct folding of protein despite accumulation of mildly deleterious mutations, and ii) an indirect mechanism due to the Dobzhansy-Müller within-protein interactions between amino acid sites, to reduce the overall fitness decline of the mutations. Evidence that endosymbiotic bacterial proteins have evolved towards structures highly robust to mistranslation errors was also observed. In conclusion, this thesis provides a mechanistic explanation for the successful survival of an innovative evolutionary strategy and highlights the intricate complex evolutionary dynamics of apparently simple organisms.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin